Leadership paradigms and nurse motivation: a comparative analysis in healthcare contexts - Sa'at, Siti Fatimah; Che Abdul Rahim, Norsyamlina; Samsudin, Norsuriani; Che Hasan, Siti Selihah; Musa, Norizan; Musa, Mazlinda (Springer, 2024)
In the dynamic healthcare landscape, effective nurse leadership is critical for optimizing patient outcomes and ensuring a motivated nursing workforce. This study examines the complex relationship between leadership styles and nurse motivation, with a specific focus on comparing the effectiveness of various leadership approaches. Additionally, the researcher explores the influence of working years and the training hospital on motivation scores under various leadership styles. To ascertain the strength of the analysis, researchers conducted assumption checking for ANOVA F-test. However, the findings revealed significant disruptions of the normality assumption, as corroborated by both Kolmogorov–Smirnov and ShapiroWilks tests (p < 0.0001). The presence of outliers further complicated matters, manifesting in skewed residual plots, deviations in the Normal QQ plot, and uneven whiskers in the Box-plot of residuals. Despite these challenges, our study comprehensively explains the observed phenomena. The histogram of residual plots also revealed a right skewed distribution, floating the idea that some observations had very large residuals. Implications for Nursing Management. The results of our study stress the paramount significance of fulfilling ANOVA assumptions and demonstrate subtle interactions among leadership styles, nurse manager motivation, and potential disruptions in assumptions on statistical data effects. Further investigations with different statistical approachesaresuggestedtoexplorethesourcesofthedifferences. This will allow us to understand more about nursing leadership that works.